ANALISIS EKONOMI JALUR DISTRIBUSI BUNGA GEMITIR (Tagetes erecta L.) DI KECAMATAN PETANG KABUPATEN BADUNG - Indah Purwati, Ninik; Mulyani, Sri; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
The objective of this research were to know 1) the various type of distribution route of marigold from farmer to consumer, 2) the handling process of distribution after the harvesting of marigold, and 3) the market margin including its profit of each distribution route of marigold from farmer to consumers. This study was a survey research. Population was farmer of marigold at Petang District, Badung Regency; and sample was farmers of marigold in farmer groups Suka Rahayu. The sampling method used purposive sampling and determine the distribution route used snowball sampling technique. The result of this research showed that there are two distribution route of marigold from Belok Sidan Village to consumers. The distribution route one was farmer-collectors-retailer-consumer, and the distribution route two was farmer-collectors-consumer. The handling process by farmer was picking, sorting, grading and packaging; by collectors was transport and temporary storage; by retail was grading. Market margin and profit margin in route 1 (one) was 5.000,00/kg and Rp. 4.115,00/kg and in route 2 (two) was Rp. 3.000,00/kg and Rp. 2.625,00/kg. The best market margin and profit margin was Rp. 3.000,00/kg and Rp. 2.625,00/kg which was found in distribution route two and the best farm gate price was 67% which was found in distribution route two. Keywords: distribution route, marigold, market margin, profit margin, and Tagetes erecta L.
Keywords: 98